Effect of weekly practice of Laghu Shankhaprakshalana Kriya (yogic bowel cleansing) on appetite in healthy adults: An exploratory study - Jaydeep Negi; Abhishek Kumar Bhardwaj (Yoga-Mimamsa)
Introduction: Shankhaprakshalana (SP) kriya is one of the shatkarma (hatha yogic cleansing practices) used to cleanse the entire gastrointestinal tract with water. This technique involves the consumption of lukewarm saline water in conjunction with dynamic yoga asanas followed by a phase of deep relaxation. Past studies have reported the benefits of SP in managing digestive issues such as constipation, migraine-associated abdominal discomfort, and irritable bowel syndrome. However, there is a notable lack of literature investigating the impact of yoga-based cleansing practices on appetite status. Objective: This study aimed to investigate the effect of Laghu Shankhaprakshalana (LSP) kriya on the appetite status of healthy individuals. Materials and Methods: Sixty-five healthy male participants naïve to yoga with a mean age of 26.92 ± 5.35 years were recruited and randomly divided into an LSP group (n = 32) and a control group (n = 33). The LSP group engaged in LSP practice once a week for 8 weeks, while the control group received no intervention. Appetite status was assessed using the Council of Nutrition Appetite Questionnaire before and after completing eight sessions of LSP. The data were analyzed using the mixed model analysis of variance followed by post hoc Bonferroni correction for a total of 60 participants (five participants withdrew from the study). Results: Following eight sessions of LSP practice, a significant increase in appetite levels was observed (p < 0.001). No significant change was found in the control group. Conclusion: This study provides preliminary evidence suggesting that LSP practice tends to enhance appetite levels in apparently healthy individuals. Further research is needed with a larger sample and physiological assessment of appetite.